The Expression Level of CCDC26 and FOXCUT Genes in Acute Lymphoblastic Leukemia - Barati, Samaneh; Mousavi, Seyed Hadi; Motallebzadeh Khanmiri, Jamal; Khani-Eshratabadi, Mohammad (Archives of Medical Laboratory Sciences, 2021)
Background and Aim: Acute lymphoblastic leukemia (ALL) is a malignant disease of lymphoid progenitor cells affecting both children and adults. Long non-coding RNAs (lncRNAs) are one kind of non-coding RNAs (ncRNAs), reported modulating the initiation or progression of diverse cancers. However, the role of CCDC26 and FOXCUT long non-coding RNAs in ALL has been unknown. In this study, we explored the expression of FOXCUT and CCDC26 lncRNAs in acute lymphoblastic leukemia cell lines. Methods: Acute T lymphoblastic leukemia cell lines, RPMI 8402, Jurkat, B lymphoblastic leukemia, Daudi, and Ramos cell lines were used. After culturing the cells, RNA extraction and cDNA synthesis were performed. The real-time PCR technique was then used to study the expression of CCDC26, FOXCUT, C-kit, and FOXC1 genes. Result: We found a significant increase of CCDC26 expression in RPMI 8402 (p <0.0001) and Ramos (p <0.05) cell lines compared to the control, while decreased expression of these genes was observed in Jurkat and Daudi cell lines. Furthermore, FOXCUT gene had a significant increase in expression in all cell lines compared to the control (p <0.01 in Daudi and RPMI 8402 cell lines) (p <0.001 in Jurkat and Ramos cell lines). Conclusion: Our results demonstrated that CCDC26 and FOXCUT genes can play a regulatory role in acute lymphoblastic leukemia and may serve as a potential diagnostic biomarker and therapeutic target of acute lymphoblastic leukemia. *Corresponding Author: Seyed Hadi Mousavi, Email: hmousavi@tums.ac.ir; ORCID: https://orcid.org/0000-0002-4686-5232 Please cite this article as: Barati S, Mousavi SH, Motallebzadeh-Khanmiri J, Khani-Eshratabdi M. The Expression Level of CCDC26 and FOXCUT Genes in Acute Lymphoblastic Leukemia. Arch Med Lab Sci. 2021;7:1-9 (e16). https://doi.org/10.22037/amls.v7.33294